Transfusion errors — can they be eliminated?. (2nd December 2019) - Bolton‐Maggs, Paula H. B.; Watt, Alison
Summary: The Serious Hazards of Transfusion haemovigilance scheme has documented adverse transfusion incidents for 22 years. Transmission of infection (three in 2018), transfusion‐related lung injury (one in 2018) and transfusion‐associated graft‐ versus ‐host disease (none since 2012) are rare. Despite national recommendations, guidelines and protocols, most incidents more than 85% of incidents are still due to errors in the transfusion process. European regulation and mandatory competency assessments have been associated with a reduction in ABO‐incompatible transfusion, but errors continue to put patients at risk. What can be done? Errors are reduced by the use of electronic identification systems. Exploration of human factors and ergonomics (HFE) results in amended approaches away from blaming individuals to a full review of the systems and environment. Research examining how transfusion is performed (work‐as‐done) compared to work‐as‐imagined (set out in protocols and guidelines) discovers where variability results in either resilience or error. All staff require HFE training, but this should be alongside employment of suitably qualified and experienced HFE professionals. Good teamwork is key and is undermined by insufficient staffing and poor morale. The five choosing wisely recommendations for transfusion (to ensure appropriate use) need to be widely disseminated to medical staff in all specialties to ensure patients participate in the decision‐making.